KORIDOR ANTAR KOTA SEBAGAI PENENTU SINERGISME SPASIAL: KAJIAN GEOGRAFI YANG SEMAKIN PENTING - Sri Rum Giyarsih (Diponegoro University, 2012)
The research conducted in the Yogyakarta-Surakarta Corridor is aimed at firstly understanding the dynamic of the corridor as one of the key factors to establish spatial synergism and secondly linking the findings with the recent discussion and future research agenda in urban geography. The investigation used survey research methods combined with in-depth interview with some key informants and scholars. The results of the research show that the potentials of the sub-regions within the corridor can play an important role and position to form spatial synergism in the corridor. The intra-regional proximity among sub-regions has impacted in increased efficiency in the production process. It also had an effect in reduced transportation cost. This research also found that some other issues in the corridor development such as the impact of climate change to regional development could be of interest in future research in urban geography and related fields